CCL2 produced by pancreatic ductal adenocarcinoma is essential for the accumulation and activation of monocytic myeloid‐derived suppressor cells. Issue 4 (15th September 2021) - Gu, Haitao; Deng, Wensheng; Zheng, Zhong; Wu, Ke; Sun, Feng
Abstract: Introduction: The development of pancreatic ductal adenocarcinoma (PDAC) is closely tied with the immune system. C‐C motif chemokine ligands (CCL) were proved to lead to immune recruitment and training. Thus, we reckoned CCL2 to be the kernel of immune suppression in PDAC tissues. Methods: We compared normal pancreatic tissues with PDAC tissues according to The Cancer Genome Atlas (TCGA) and clinical samples. Flow cytometry was used to identify M‐MDSCs. We further demonstrated immune suppression of M‐MDSCs according to proliferation rates of CD8 + T cells/CD4 + T cells. Levels of reactive oxygen species (ROS) and Arginase were also tested by flow cytometry, enzyme‐linked immunosorbent assay, and western blot analysis. We also analyzed the specific mechanisms by cluster analysis after CCL2 stimulating M‐MDSCs. Results: We found that CCL2 highly increased in PDAC tissues. CCL2 is positively related to CD33 and CD14, markers of monocytic myeloid‐derived suppressor cells (M‐MDSCs). We have demonstrated that CCL2 recruited M‐MDSCs into PDAC tissues both in vitro and in vivo. M‐MDSCs recruitment is accompanied by sustained immune suppression. Furthermore, we have found that M‐MDSCs impeded T cell proliferation and produced high levels of ROS and Arginase, which can be enhanced by CCL2. Mechanistically, CCL2 stimulated M‐MDSCs led to a significant upregulation of genes, a large part of which accumulated in the mitogen‐activated protein kinase signaling pathway. Treatment of aloesin, MAPK signaling inhibitor, relieved the associated immunosuppressive phenotype induced by CCL2. Conclusions: Our study indicates that PDAC cells produced CCL2, which promoted localized M‐MDSC recruitment and immune suppression, thereby promoting tumor progression. Abstract : Our data indicate that CCL2 performs a significant role in PDAC progression by recruiting and activating M‐MDSCs. Targeting MDSCs is able to improve antitumoral immunological responses providing with potential applicability of immune‐based combination therapies against an extensive spectrum of solid tumors. These miscellaneous approaches might prove available for tumor therapeutics against solid carcinomas in which M‐MDSCs perform a major role in immune evasion of tumors. These results are promising and need further assessment of the M‐MDSCs‐targeting combination or vaccination approaches for the whole therapeutic capacity of these tactics in PDAC and other carcinomas Highlights: CCL2 is significantly upregulated in colon adenocarcinoma CCL2 influences M‐MDSC recruitment and functionality in colon adenocarcinoma CCL2 stimulates immune‐suppressive functions of M‐MDSC by activating MAPK signaling